The Hepatotoxicity of Alantolactone and Germacrone: Their Influence on Cholesterol and Lipid Metabolism in Differentiated HepaRG Cells - Zárybnický, Tomáš (Nutrients, 2020)
The sesquiterpenes alantolactone (ATL) and germacrone (GER) are potential anticancer agents of natural origin. Their toxicity and biological activity have been evaluated using the differentiated HepaRG (dHepaRG) cells, a hepatocyte-like model. The half-maximal inhibitory concentrations of cell viability after 24-h treatment of dHepaRG cells are approximately 60 µM for ATL and 250 µM for GER. However, both sesquiterpenes induce reactive oxygen species (ROS) formation in non-toxic concentrations and significantly dysregulate the mRNA expression of several functional markers of mature hepatocytes. They similarly decrease the protein level of signal transducer and activator of transcription 3 (STAT3), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and their transcription target, intercellular adhesion molecule 1 (ICAM-1). Based on the results of a BATMAN-TCM analysis, the effects of sesquiterpenes on cholesterol and lipid metabolism were studied. Sesquiterpene-mediated dysregulation of both cholesterol and lipid metabolism was observed, during which these compounds influenced the protein expression of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) and sterol regulatory element-binding protein 2 (SREBP-2), as well as the mRNA expression of HMGCR, CYP19A1, PLIN2, FASN, SCD, ACACB, and GPAM genes. In conclusion, the two sesquiterpenes caused ROS induction at non-toxic concentrations and alterations in cholesterol and lipid metabolism at slightly toxic and toxic concentrations, suggesting a risk of liver damage if administered to humans.